2020
DOI: 10.2147/cmar.s254944
|View full text |Cite|
|
Sign up to set email alerts
|

<p>LncRNA PTCSC3 and lncRNA HULC Negatively Affect Each Other to Regulate Cancer Cell Invasion and Migration in Gastric Cancer</p>

Abstract: Background: LncRNA PTCSC3 (PTCSC3) inhibits thyroid cancer cervical carcinoma and glioma, while its roles in gastric cancer are unknown. Studies have reported that HULC could serve as a potential biomarker for the diagnosis and prognosis of gastric cancer (GC). Our study aimed to investigate the potential interaction between PTCSC3 and HULC in gastric cancer. Methods: This study enrolled 77 gastric cancer patients at the First Affiliated Hospital of Anhui Medical University from January 2016 to January 2018. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, in thyroid cancer, PTCSC3 is downregulated in the plasma of patients with gastric cancer and can regulate multiple pathways, such as the Wnt and STAT3 signaling pathway, to impact cancer cellular behaviors including viability, migration and invasion ( 12 , 26 , 27 ). In addition, PTCSC3 is downregulated in gastric cancer and can interact with lncRNA HULC, HOXA11-AS and Linc-pint to suppress invasion and viability of cancer cells ( 28 , 29 ). Moreover, recent studies suggested that PTCSC3 is a potential biomarker for the treatment and prognosis of gastric cancer ( 29 , 30 ), whereas its role in TNBC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in thyroid cancer, PTCSC3 is downregulated in the plasma of patients with gastric cancer and can regulate multiple pathways, such as the Wnt and STAT3 signaling pathway, to impact cancer cellular behaviors including viability, migration and invasion ( 12 , 26 , 27 ). In addition, PTCSC3 is downregulated in gastric cancer and can interact with lncRNA HULC, HOXA11-AS and Linc-pint to suppress invasion and viability of cancer cells ( 28 , 29 ). Moreover, recent studies suggested that PTCSC3 is a potential biomarker for the treatment and prognosis of gastric cancer ( 29 , 30 ), whereas its role in TNBC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In GC tissues and cell lines, downregulation of PTCSC3 has been observed in several studies [ 20 23 ]. The role of lncRNA PTCSC3 in GC is schematically shown in Fig.…”
Section: The Expression Of Ptcsc3 In Different Cancersmentioning
confidence: 97%